Incidence of breast nodules in young women from 15 to 35 years: a literature review - Medeiros, Ana Caroline Florentina; Bettes, Paulo Sergio Loiacono (Seven Editora, 2023)
Nodules are tumors that may present cystic or solid content. That benign mammary feature constitutes up to 80% of all palpable lumps existent in women. Among these nodules, fibroadenoma is the most common in women aged between 15 and 35 years old. Thus, it’s important for the scientific community and the population to the study parameters, such as the growth of young people that presents mammary nodules, the risk factors, the most frequent types in young women, as well as the diagnostic description. This study has an exploratory qualitative approach, done through an integrative revision of the scientific literature available in Portuguese and foreign languages from 1988 to 2020 about mammary nodules in young women. The importance of carrying out this research is justified by the analysis of the mammary nodule incidence in young women over the years, and thereat verify if there were precursor wounds of mammary cancer. Therefore it is possible to find if there is an increase in its incidence and perform an early diagnosis to attend to the antecedence of the symptoms of this benign disease. In addition, if there is a history that biases the increase of cancer risk in the future, it’s possible to prevent it based on the identification of high-risk lumps. This topic has an authentic profile, with no referent article, and has not been discussed in the existent platforms, so it makes this relevant and innovative DOI: https://doi.org/10.56238/devopinterscie-091